Análise econômica de uma função de produção milho na região de patos de Minas, Minas Gerais, ano agrícola 1964/65 - Batista de Oliveira, Evonir; Fagundes de Souza, Antônio (Revista Ceres, 2025)
The present study attempts to identify actual use of agricultural resources in the production of corn in the area of Patos de Minas, Zone of Alto Paranaíba, State of Minas Gerais and analyze the economic efficiency with which these resources are being used. It also attempts to identify the possible changes which can increase this efficiency. The area was selected because of its importance in corn production.